MANAJEMEN USAHA DAN STRATEGI PEMBERDAYAAN INDUSTRI KECIL PRODUK MAKANAN DI KOTA PALEMBANG - Umar Hamdan; Yulia Hamdaini Putri (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2012)
ABSTRACT The aims of this research are to observe, analyze, and discuss the performance of business management and strategic choice for small scale industry for food products (crispy bakes, cake and bread,soya-beans and toffu) in Palembang City. This research applies survey method by using 30 small scale business- holders as sample respondents. Data was analyzed by using quantitative and qualitative methods, such as statistical tabulation, financial ratio analysis, and SWOT analysis. The research findings as follows: 1) the small scale industry holders have simple organization and management, 2) most of them are having some problems in getting production input, absolette facilities, and low quality product; 2) the demand on small scale industrial products is still increasing continuously, 3) competition among small businesses is very tight, 4) most of them are facing lack of working capital and investment fund to expand their businesses and refinancing new production facilities To empower the owners of small scale industry for food products in Palembang City, they can choose SO, ST, WO, and WT strategies that fit to their businesses. We, researchers, recommend that the small scale industry business holders have to: 1) do more creative and eficiency in production, 2) raise fund for capital needed from foster parent company and/or local bank, 3) receive business management training program from related government agency, private institution, business association, and/or university. We also recommend that the related local government institutions have to encourage people to do fishery farming dan soybean farming. Finally, management of Primkopti in Palembang has to cooperate with BULOG in soybean supply.